Innovative Technology for Preparing Washing Liquid in the Course of Drilling - Davydenko, A.N.; Kamyshatsky, A.F.; Sudakov, A.K. (Science and Innovation, 2024)
A technique for washing liquid preparation has been designed. The advantages of the hydrodynamic super-cavitation technique to be used for preparation of washing liquids in the course of drilling have been described. The theoretical research has enabled setting parameters and designing a cavitation disperser. The results of theoretical research have been confirmed in practice and laid foundation for creating a technique for preparing washing liquid. The cavitation disperser has been tested in production environment.